Correlation between vascular endothelial growth factor (VEGF) expression with histopathological findings in osteosarcoma - Fikar Arsyad Hakim; Yuni Artha Prabowo Putro; Yudha Mathan Sakti; Rahadyan Magetsari; Irianiwati Widodo; Ery Kus Dwianingsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Vascular endothelial growth factor (VEGF) expression is associated with malignancy progression, metastasis, and poor prognosis in many malignancies, including osteosarcoma. However, studies concerning correlations between VEGF expression and histopathological prognostic factors ofosteosarcoma are limited. This study aimed to evaluate the correlations between VEGF expression and histopathological findings in osteosarcoma’spatients.This was a cross-sectional study using formalin-fixed paraffin embedded (FFPE) samples of 32 osteosarcoma’s patients from Dr. Sardjito General Hospital, Yogyakarta. Histopathological findings of specimens were re-evaluated by two independent observers, recorded for the subtypes, invasiveness, grading, mitotic counts, and tumor infiltrating lymphocytes (TIL). Expression of VEGF was determined based on immunostaining and evaluated using immunoreactivity score (IRS).Chi-square and Spearman correlation test were used to analyze the association between variables. Range of VEGF expression score was 0 to 11, with mean 5.09. Significant negative correlation between the VEGF expression and TIL was observed (p=0.046). However, there was no significant correlations between the VEGF expression and osteosarcomas subtypes, invasion, grading or mitotic counts (p> 0.05). In conclusion, the VEGF expression is associated with TIL. Further study is needed to evaluate the roles of VEGF and lymphocytes in osteosarcoma development dan progression in order to better understand of the role of VEGF in immunotherapy of osteosarcoma.